Driving Factors Behind the Issuance and Use of Islamic Credit Cards in Indonesia: The Role of Consumerism - I Muhammad, Nurdin; Yetty, Yetty; Suar, Abi; Zainuddin, Zainuddin (Owner : Riset dan Jurnal Akuntansi, 2024)
The issuance of Sharia credit cards has sparked considerable debate within society. Critics argue that issuing credit cards through Islamic banks fosters a culture of consumerism and has the potential to increase non-performing financing ratios (Non-Performing Financing-NPF). Conversely, supporters assert that these credit cards facilitate transactions for Islamic bank customers. This research employs a mixed-method approach with a Sequential Exploratory design, characterized by the collection and analysis of quantitative data in the first stage, followed by the collection and analysis of qualitative data in the second stage. The data processing results indicate that both the issuance variable (X1) and usage variable (X2), independently and jointly, influence consumerism (Y). Moreover, public consumerism driven by the use of Sharia credit cards significantly impacts economic transaction behavior. The study concludes that the issuance and utilization of Sharia credit cards significantly affect consumer behavior, leading to increased consumerism.